SOCIO-CULTURAL SPACE OF THE MOUNTAIN SCHOOL AS A HISTORICAL, ETHNO-SOCIAL, EDUCATIONAL AND CULTURAL PHENOMENON AND SUBJECT OF SCIENTIFIC STUDIES - Chervinska, Inna (Mountain School of Ukrainian Carpaty, 2020)
The article, based on a holistic retrospective analysis of scientific literature, the experience of secondary schools in the mountainous region of the Ukrainian Carpathians, to reveal the features of the socio-cultural space of the mountain school as a historical, ethnosocial phenomenon and subject of scientific studies. It is pointed out that the issue of formation, development and design of spaces is one of those that are most actively developed in the modern psychological and pedagogical literature. Within its framework, the theme of the evolution of regional socio-cultural spaces is clearly distinguished and acquires an independent status. The author emphasizes that in philosophical, culturological, sociological research, both fundamental and applied, the term "socio-cultural space" is used as a source category that does not require additional theoretical argumentation, as a collective image that contains all the diversity of the existing reality. Attention is emphasized that through the theoretical analysis of the source base and methodological construct of the sociocultural space of the mountain school the essence of the concept of "sociocultural space" as a subject of historical, ethnosocial, educational and culturological studies is substantiated. The use of such research methods as: search and bibliographic - in order to study library catalogs, bibliographic publications; content analysis - to clarify the state of development of the problem, the formulation of the terminology of basic concepts and conceptualization of the main provisions; analysis of the content of pedagogical activity of educational institutions, generalization of own experience of cooperation with teachers and students of mountain schools. It is generalized that the spatial development and analysis of the life of people living in a certain socio-cultural space are among a number of the most pressing issues for modern society. Pedagogical science uses a large number of approaches and methods of spatial analysis, which allow studying socio-pedagogical problems and to some extent contribute to their effective solution.